Integration of Adjectives to Learn Grammatical Gender for Object Categorization in Urdu for Balti Speakers - Basit, Abdul (Universitas Ahmad Dahlan, 2020)
This quantitative research is an attempt to explore the possibilities to decrease the level of difficulty for Balti language speakers in object categorization while they learn Urdu language as their L2. Purpose of this research is to know that how chunking technique can help the Balti speakers remember the grammatical gender of different inanimate objects while keeping in mind their adjective-noun pairs. This is an experimental study and population for this research is comprised of all Balti language speakers living in Lahore. Simple random sampling technique is used to select the sample and teaching sessions are conducted by the researcher to teach experimental and controlled groups. Findings of this study show that chunking technique is beneficial to be used for L2 learners of Urdu language especially if their L1 doesn’t have the concept of grammatical gender. In conclusion, it is recommended through this research to apply the same technique of linking adjectives with nouns in pedagogical approach for the Balti speakers who intend learn Urdu as their L2 with the help of their curriculum.